Characteristics of the labor market in Kosovo and Europe - Haziri, Artan (European Journal of Economics and Business Studies, 2015)
The level of economic development of Kosovo is reflected in a delay of many economic parameters in place which results even in the strangulation of the labor market as the biggest challenge in Kosovo. Would not mind that the most worrying aspect of the labor market in Kosovo is the high unemployment rate which reflects with the numerous problems in Kosovo society. The labor market in Kosovo was consistently followed by a different set of anomalies which have led to the raising concerns of the Kosovo population which are reflected not only by the unemployed, but also the active part of the population which in the absence of functioning of the collective contract, failure of unions, low average wage and a series of violations of workers' rights more and more is undergoing development gap in the labor market. Kosovo is the highest rate of unemployment in the region which is around 50 percent. And when we consider the composition of contingent labor, such as very young population which annually makes contingent labor increases in parallel with this also increases the rate of demand for labor and immigration as the feature itself, then the approach should become much more serious. From the statistical data shows that unemployment is the highest in young persons (16-24 years), this age includes about 40 percent of the total number of unemployed. Also, the unemployment rate appears too high even to women though are not very active. Viewing these data mean that unemployment in Kosovo is mostly long term and it is estimated that about 80 percent of the unemployed are long-term unemployed for more than 12 months. This condition appears as unemployment will remain for a long time the main challenges of the economy and society in general.
Keywords: Unemployment, employment policies, work force, labour market, SOK